Rekontekstualisasi Fikih Keluarga di Era Modern: Studi Perbandingan Indonesia, Tunisia, dan Turki - Hadaiyatullah, Syeh Sarip; Fikri, Arif; Dharmayani, Dharmayani; Karini, Eti; Ismail, Habib (Moderasi : Journal of Islamic Studies, 2024)
The recontextualization of family law in Muslim-majority countries has gained significance amidst contemporary social, political, and legal transformations. This study examines the reforms of family law in Indonesia, Tunisia, and Turkey, focusing on gender equality, women's rights, and the limitation of polygamy. Employing a qualitative methodology with a comparative approach, data were gathered from literature reviews, legal documents, and regulations in each country. In Indonesia, the Compilation of Islamic Law (KHI) integrates Islamic jurisprudence with local traditions and human rights principles. Tunisia’s Code du Statut Personnel (CSP) replaces traditional Islamic family law with a secular system emphasizing gender equality. In Turkey, the secular Turkish Civil Code incorporates some elements of Islamic jurisprudence, particularly in inheritance. The findings reveal that while all three countries aim to improve women's positions and align family law with social progress, their approaches differ based on socio-cultural and political contexts. The study concludes that the recontextualization of family law in these countries reflects efforts to balance tradition and modernity, offering improved protection for women's rights through varying local adaptations. These findings contribute to a deeper understanding of family law dynamics in Muslim societies and provide recommendations for reform in similar contexts.